The Macrostructure and Register of Chinese, English and Polish School Certificates and University Diplomas - Grzybek, Joanna; Matulewska, Aleksandra (Investigationes Linguisticae, 2006)
This paper presents the macrostructure of Chinese, English and Polish school certificates and university diplomas (Hughes, Varó 2002) in the aspect of translation. The language and vocabulary used in Chinese, Polish and English certificates and diplomas are researched into. The conclusions are that the historically conditioned differences in legal realities in China, Taiwan, Poland (the impact of the partitions and the Communist regime) and the English-speaking countries affect the structure and contents of such certificates and diplomas. Thus, Polish certificates and diplomas are more similar to British and American ones. However, certificates and diplomas executed in China have different macrostructure (they are in a form of a book). As a consequence, some legal terms and expressions which appear in them do not occur in Polish and English.